The Rural Migration from Villages in Kastamonu, Turkey; the Reasons and Effects - Sumayyah Alsharif Ali Alshaybani; Aydın, Miraç (Zenodo, 2022)
ABSTRACT Migration is one of the most important issues in Turkey today. Notably, the state forest enterprises are affected by the social, economic, and ecological dimensions of migration; these enterprises find it increasingly difficult to find labor force to operate effectively in the forestry activities with each passing day. And due to the emigration from Kastamonu province, the population of villages decreases, which causes several changes in land use. These changes are mostly evident in forest and agricultural areas. The purpose of this study is to identify, the most important reasons and motives that lead to the migration process, the problems and effects of the migration process from the study area, shedding light on some forest villages subject to migration, then showing the problems these villages suffer, and trying to put measures to guide migration currents, and help cope in the conditions facing forest villagers. In order to reach a deeper and more comprehensive understanding of the phenomenon of migration.
Keywords: 11. Sustainability; 15. Life on land